2001
DOI: 10.1038/sj.ijo.0801466
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat and coronary pathology in male adolescents

Abstract: OBJECTIVE: To ®nd out whether coronary atherosclerotic lesions and their precursors in male adolescents are associated with the amount of mesenteric and omental fat. SUBJECTS: A series of 40 forensic autopsy cases of ante-mortem healthy boys of 13 ± 19 y of age were investigated. METHODS: Body height and weight, waist and hip circumferences and the thickness of the abdominal subcutaneous fat were measured, the body mass index (BMI) and waist-to-hip ratio (WHR) were calculated, and omental and mesenteric fat de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 21 publications
1
29
0
6
Order By: Relevance
“…From a clinical point of view, it is important to note that maximal density of macrophages/mm 2 in atherosclerotic lesions is associated with visceral obesity (30), reduced coronary flow reserve related to body fat distribution and insulin resistance (31), and the MetS associated with lipid-rich plaque (32). In a systematic review and meta-analysis of longitudinal studies (33), it has been reported that individuals with the MetS are at increased risk of a cardiovascular events and death (relative risk 1.78).…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…From a clinical point of view, it is important to note that maximal density of macrophages/mm 2 in atherosclerotic lesions is associated with visceral obesity (30), reduced coronary flow reserve related to body fat distribution and insulin resistance (31), and the MetS associated with lipid-rich plaque (32). In a systematic review and meta-analysis of longitudinal studies (33), it has been reported that individuals with the MetS are at increased risk of a cardiovascular events and death (relative risk 1.78).…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…components of the metabolic syndrome [2]. It is generally considered that the unfavourable prognosis in subjects with abdominal obesity is due to large amounts of intra-abdominal fat [3][4][5][6]. Human omental fat cells display a high number of beta-adrenergic receptors and reduced antilipolytic effect of insulin, compared with subcutaneous fat cells, resulting in a high release of fatty acids from this fat cell depot [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In all, 52 female cadavers aged between 18 and 49 y were examined and data were obtained from police records and medical records, as described previously. 10,16 The cases consisted of 11 sudden deaths from unexpected natural causes (four cases of subarachnoid hemorrhage, two cases of pulmonary embolism, three cases of epilepsy and two cases of coronary artery disease with acute myocardial infarction), 19 accidental deaths, 20 suicides and two homicides. None of the subjects were reported to have had any hormone replacement therapy and none of them were pregnant.…”
Section: Subjectsmentioning
confidence: 99%
“…16 Body mass index (BMI; kg/m 2 ) and waist-to-hip ratio (WHR) were calculated from these measurements.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%